Exploring the Nursing Factors Related to Ventilator-Associated Pneumonia in the Intensive Care Unit - Yin, Yanling; Sun, Meirong; Li, Zhe; Bu, Jingjing; Chen, Yuhong; Zhang, Kun; Hu, Zhenjie (Frontiers in Public Health, 2022)
Objective The purpose of this study was to investigate the key nursing factors associated with ventilator-associated pneumonia (VAP) in critical care patients. Methods Through the quality control platform of Hebei Province, questionnaires were sent to intensive care nurses in 32 tertiary hospitals in Hebei Province, China to collect data concerning the incidence of VAP and the status of the nursing staff. All the data were analyzed using an independent t-test and a one-way analysis of variance (ANOVA). The Pearson correlation coefficient was used to analyse the correlation between the nursing factors and the incidence of VAP. Multivariate logistic regression analysis was used to determine the risk factors affecting VAP. Results In terms of nursing, the incidence of VAP was affected by the differential nursing strategies. Multivariate logistic regression analysis showed that the incidence of VAP was significantly associated with the following six variables: the ratio of nurses to beds (p = 0.000), the ratio of nurses with a bachelor's degree or higher (p = 0.000), the ratio of specialist nurses (p = 0.000), the proportion of nurses with work experience of 5–10 years (p = 0.04), the number of patients nurses were responsible for at night (p = 0.01) and the frequency of oral care (p = 0.000). Conclusion The incidence of VAP is closely related to nursing factors. In terms of nursing human resources, even junior nurses (less experienced nurses) can play an essential role in reducing VAP. In addition, to reduce VAP, the number of patients that nurses are responsible for at night should be reduced as much as possible, and improving nursing qualifications.